Triagem da hepatite B em doadores de sangue no Estado do Amazonas - Belota, Rosa Cristina Caldas (2020)
Hepatitis B is an infectious disease of worldwide importance and of great interest for transfusion medicine. The Amazon region has areas of high endemicity, outlining a worrying scenario for local transfusion safety. However, results profiles in serological and molecular screening make us question whether they are associated with infection by the hepatitis B virus. The present study is justified by the need to verify whether results profiles in screening for hepatitis B present or not detectable viral load and its possible impact on public health and stocks of blood components. Objective: To investigate the prevalence of Hepatitis B in blood donors from the blood center of Amazonas (HEMOAM) according to the reactivity for NAT-HBV, HBsAg, Anti-HBc and viral load in the period from January 2015 to December 2018. Material and Methods: Descriptive, retrospective study of HEMOAM donor records with positive results and their correspondence with the results of viral load obtained through the electronic medical record system of the Tropical Medicine Foundation Dr. Heitor Vieira Dourado (FMT-HVD). Results: 230,591 blood donations were analyzed, of which 3,932 (1.7%) were retained in serological and molecular screening with 3,104 (1.34%) of the retentions showing the following results NAT HBV: 3.02%; HBsAg: 9.92% and Anti-HBc: 93.8%. Among the reactive donors, 314 (10.11%) had a forwarding profile for the detection of viral load in the FMT-HVD, however the records of only 73 (23.1%) were found, of which 95.8% with the profile: NAT HBV positive / HBsAg positive / Anti-HBC positive and 100% with the profile: NAT HBV negative / HBsAg positive / Anti-HBC positive had detectable viral load whereas 100% of donors with only HBsAg positive did not show viral load. Conclusion: In this study it was possible to verify the importance of the need for traceability of blood donors forwarded for the detection of viral charge in the reference center, because despite a considerable amount of reactive donors, to demonstrate the importance of hepatitis B in the state of Amazonas, unexpected results were observed regarding the presence or absence of viral load in certain reactivity profiles in serological and molecular screening, which may be impacting both the stocks of blood components and public health with the detection of new cases of asymptomatic hepatitis B